Leveraging Contract Farming for Supply Chain in India: a Case of Gherkin Production - Gummagolmath, KC; Sharma, Purushottam; ., Shalendra (Journal of Agricultural Extension Management, 2018)
The cultivation of gherkin is undertaken in 20 districts of Karnataka. The farmers cultivating gherkin mostly belong to the category of marginal (37 per cent) and small farmers (53 per cent). These farmers take up less than one acre since the crop is labour intensive. Firms provide credit facilities for secondary expenses in addition to inputs such as seeds, fertilizers, chemicals and other cash inputs. The average yield varies from 3.60 tonnes per acre to 3.85 tonnes per acre. All the categories of contract fanners who produced gherkin along with other crops had higher income compared to non-contracting farmers. The average income of marginal fanners was Rs. 48,105 followed by small farmers (Rs. 49,156) and big farmers (Rs. 70,238). In the case of non-contract farmers the net income of marginal, small and big land holders was Rs. 30,185, Rs. 38,454 and Rs. 57,003 respectively. The minimum income and the maximum income of the contracting marginal farmers was Rs. 35,313 and Rs. 63,005 respectively. In case of noncontracting marginal farmers it was Rs. 26,531 and Rs. 57,730 which is lesser than the contracting farmers. The buyback system with a pre-agreed price reduced the risk in production and provided good income for a better standard of living. Most of the farmers are firm about continuing the production of gherkin in future years also. The farmers expressed that the income of the family has increased after undertaking the cultivation of gherkin and they could acquire required assets and enjoy a better standard of living. The successful models like gherkin model in Karnataka should be encouraged and extended progressively to the rest of the agricultural commercial enterprises for mutual benefit of the farmer and the consumer in particular and the development of Indian agriculture in general. Introduction